Hydrogel micropillars with integrin selective peptidomimetic functionalized nanopatterned tops: a new tool for the measurement of cell traction forces transmitted through αvβ3- or α5β1-integrins - Rahmouni, Sabri; Lindner, Aaron; Rechenmacher, Florian; Neubauer, Stefanie; Sobahi, Tariq Rashad Ali; Kessler, Horst; Cavalcanti-Adam, Elisabetta A.; Spatz, Joachim P. (Advanced materials, 2013)
Poly(ethylene glycol) micropillars with gold nanopatterns on top are functionalized with two integrin selective ligands. This platform is a powerful new tool to determine the specific contribution of traction forces involved in cell adhesion mediated by α5 β1- and αvβ3- integrins. Cells adherent via α5 β1-integrins have a tendency to exert higher maximum forces than cells adhering via αvβ3-integrins.
Gesehen am 05.01.2022